2014
DOI: 10.15625/0866-7160/v29n4.5402
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic plants from Vetnam, sources of natural products for industry

Abstract: aromatic plants produce by vapour distillation or other processes essential oils which are products with high commercial value used in the natural product industries such flavour and fragrance, perfumes and cosmetics industries as well as pharmaceutical industry. The aim of this study was to characterise some aromatic plants from Vietnam through the chemical composition of their essential oils. We got interested in essential oils which contained a main component with high to ultra high content, susceptible to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
1
1
Order By: Relevance
“…The citronellal content in lemon eucalyptus essential oil used in this study was different from other studies. Specifically, the citronellal content in this study was lower than the results reported in Vietnam by Tran Minh Hoi et al (78.2%) [13], and Ho Dung Manh et al (78.6%) [14], higher than the results reported by Tran Thi Nhu Trang et al (62%) [15]. In addition, the citronellal content in this study was lower than the citronellal content (74%) in the lemon eucalyptus essential oil used to synthesize PMD in the study of Jeremy Drapeur et al [6].…”
Section: Analysis Of Essential Oils Compositioncontrasting
confidence: 89%
See 1 more Smart Citation
“…The citronellal content in lemon eucalyptus essential oil used in this study was different from other studies. Specifically, the citronellal content in this study was lower than the results reported in Vietnam by Tran Minh Hoi et al (78.2%) [13], and Ho Dung Manh et al (78.6%) [14], higher than the results reported by Tran Thi Nhu Trang et al (62%) [15]. In addition, the citronellal content in this study was lower than the citronellal content (74%) in the lemon eucalyptus essential oil used to synthesize PMD in the study of Jeremy Drapeur et al [6].…”
Section: Analysis Of Essential Oils Compositioncontrasting
confidence: 89%
“…NMR spectra were recorded on a Bruker (AvanceNEO). 1 H and 13 C spectra were determined at 600 and 150 MHz, respectively, and were recorded in CDCl3. NMR spectral data of PMD: C NMR 20.3 (CH2), 22.2 (CH3), 25.5 (CH), 28.6 (CH3), 28.9 (CH3), 34.9 (CH2), 42.5 (CH2), 48.2 (CH), 67.9 (CH), 73.2 (C).…”
Section: Nmrmentioning
confidence: 99%